3-D modelling of the coaxial one-side resistance spot welding of AL5052/CFRP dissimilar material. (August 2021) - Ren, Sendong; Ma, Yunwu; Ma, Ninshu; Saeki, Shuhei; Iwamoto, Yoshiaki
Abstract: Coaxial one-side resistance spot welding (COS-RSW) is an advanced technique for joining CFRP/metal dissimilar materials. In the present work, a three-dimensional model was developed based upon an in-house finite element code JWRIAN-SPOT to simulate the multi-physical process of the COS-RSW. The thermal cycle and joining strength of COS-RSW joints with different welding parameters were measured experimentally. The sensitivity of material properties of electrode couple and component of accumulated heat generation were discussed in detail. The predicted thermal cycles presented a reasonable agreement with measurements, which also explained the influence of welding parameters on temperature field. The joining strength of COS-RSW joints can be evaluated qualitatively via the area of effective molten zone, which reached about 20 MPa with a 4800 A welding current. The column and cylinder electrodes determined the peak value of interface temperature and molten zone area, respectively. The cylinder electrode was suggested to be fabricated by a high resistivity material to generate sufficient Joule heat. Moreover, the SUS304 electrode and its contact zone provided more than 70% of the entire heat generation. The materials of electrode couple should be determined carefully when employing COS-RSW for joining CFRP and other metals. Graphical abstract: Unlabelled Image Highlights: A 3-D model of COS-RSW was established based upon an in-house finite element code JWRIAN-SPOT The joining strength of COS-RSW joints shows similar variation tendency to the area of effective molten zone The column and cylinder electrodes determine the maximum interface temperature and molten zone area, respectively The SUS304 electrode and SUS304-AL5052 interface generate more than 70% of the total Joule heat